HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP PESERTA PROLANIS DIABETES MELLITUS TIPE 2 TERHADAP KEPATUHAN PROTOKOL KESEHATAN COVID - 19 DI KLINIK IMAN - ANGGI SRI REJEKI; SHAHRUL RAHMAN (LP2MTBM MAKARIOZ, 2021)
COVID-19 is an acute respiratory disease that was discovered in early December 2019 and is called a public healthemergency by WHO. Patients with type 2 diabetes mellitus are susceptible to infection with COVID-19 because it is acomorbid disease. To identifying the relationship between the level of knowledge and attitudes of participants in Prolanis type2 diabetes mellitus to compliance with the COVID-19 health protocol in the IMAN clinic. Analytical descriptive using crosssectionaldesign. The hypothesis test used is the Chi Square Test. The questionnaire that has been validated with thenumber of respondents is 38 samples. The results showed 28 people (93.3%) had a good level of knowledge in the obedientcategory with a p value of 0.004 and as many as 31 people (91.2%) had a positive attitude in the obedient category with a pvalue of 0.009. There is a relationship between the level of knowledge and attitudes towards compliance with the COVID-19health protocol.